ASSESSING THE IMPACT OF STRENGTH TRAINING ON SHOULDER PATHOLOGY IN ATHLETES - FAROOQ, B; HAMMAD, AR; QURESHI, ZH; SHAHEEN, B (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in Nishtar Medical Hospital Multan, MMDC Multan & FMU Faisalabad from January 2022 to July 2022 to assess the effect of persistent resistance training of the shoulder on undetected pathologies. A total of 10 subjects were included in the study. The participants underwent clinical and radiographic examinations. The clinical assessment also included UCLA, SST, and CMS tests. An experienced radiologist reviewed the MRI images. Analysis showed that the average duration of bodybuilding was 10.6 years. Of the 20 shoulders, 17 (85%) had no pain or limitation, and 3(15%) had mild pain because of recent heavy loading and exercise. All participants had maximum SST scores and UCLA Activity Test for both shoulders. Regarding radiological outcomes, MRI results reported 34 abnormalities. The results show that bodybuilding increase pathologies of AC joint in athletes, though other shoulder complex structures are unaffected.